New API Helps with Multicore-Chip Communications. (Computer (00189162), 2009)
This article discusses an application programming interface (API) designed for use in multicore computer chips that is called MCAPI. This system, designed by the Multicore Association, is intended to encourage vendors to develop programs for multicore-chips by allowing them to write to a common API without concern for the underlying hardware. MCAPI was developed by a partnership that included PolyCore Software Inc., Express Logic Inc., and Wind River Systems Inc.